Prevalence and Associated Factors of Diabetic Retinopathy in People with Type 2 Diabetes Attending Community Based Diabetic Retinopathy Screening in Greater Bandung, Indonesia - Halim, Aldiana; Syumarti, Syumarti; Rini, Mayang; Ratnaningsih, Nina; Iskandar, Erwin; Sovani, Iwan; Virgana, Rova; Dahlan, Muhammad Rinaldi (International Journal of Retina, 2022)
Introduction: Determine the prevalence and associated factors of diabetic retinopathy (DR) among people with type 2 diabetes. Design: Cross-sectional study Methods: We obtained data of people with type 2 diabetes retrospectively from a community-based DR screening database in Greater Bandung, Indonesia. We encoded the two fields mydriatic 45-degree fundus images to estimate prevalence. The associated factors analysis used multivariate logistic regression. Results: We screened a total of 4,251 people with type 2 diabetes from January 2016 to December 2019. The overall age-standardised prevalence of any DR was 30.7% (95% CI: 28.7%-32.8%) and vision-threatening DR 7.6% (95% CI: 6.5%-9.0%). The following factors were associated with a higher prevalence of any DR: ages 50+ (OR:1.37; 95% CI:1.05-1.77), duration of diabetes five to ten years (OR:1.38; 95% CI:1.11-1.71) and more than ten years (OR:1.40; 95% CI:1.13-1.73), and postprandial blood glucose 200 mg/dl and higher (OR:1.27; 95% CI:1.03-1.52). The following factors were associated with a higher prevalence of vision-threatening DR: duration of diabetes five to ten years (OR:2.01; 95% CI:1.39-2.91) and more than ten years (OR:1.86; 95% CI:1.28-2.71), postprandial blood glucose 200 mg/dl or higher (OR:1.52; 95% CI:1.05-2.21) and systolic blood pressure 180 mmHg or higher (OR:2.67; 95% CI:1.16-6.17). Conclusion: Diabetic retinopathy is prevalent among people with type 2 diabetes. People with diabetes should regulate their blood glucose and blood pressure to prevent retinopathy related vision loss.